Answer:
The standard form of the equation is 49t² - 75t + 3 = 0
The solution of the equations are 1.49 and 0.041
Explanation:
* Lets explain how to solve the problem
- The standard form of the quadratic equation is ax² + bx + c = 0,
where a , b , c are constant and a can not be 0
∵ The quadratic equation is -4.9t² + 7.5t + 1.8 = 2.1
- Lets make the left hand side equal to 0
∵ -4.9t² + 7.5t + 1.8 = 2.1 ⇒ subtract 2.1 from both sides
∴ -4.9t² + 7.5t - 0.3 = 0 ⇒ multiply each term by -10
∴ 49t² - 75t + 3 = 0
* The standard form of the equation is 49t² - 75t + 3 = 0
∵ ax² + bx + c = 0
∴ a = 49 , b = -75 , c = 3
- Lets use the formula
to solve
the equation
∴
![x=\frac{-(-75)+\sqrt{(-75)^(2)-4(49)(3)}}{2(49)}=1.49](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5melrhpj7f27x6w14qb7arbn4ndypxbn85.png)
∴
![x=\frac{-(-75)-\sqrt{(-75)^(2)-4(49)(3)}}{2(49)}=0.041](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vd7as0znxqdth89jh20je39xy792uvc8e6.png)
* The solution of the equations are 1.49 and 0.041